Apprendere la concorrenza: l'emigrazione nei manuali scolastici europei tra la fine dell'Ottocento e i primi decenni del Novecento - Paolo Bianchini (Firenze University Press, 2016)
The paper aims to investigate the way in which competition between European nations was presented and justified in school between 1870 e 1920. In this meaning, it will be analyzed a sample of textbooks used in primary and secondary schools in three countries - France, Italy and Spain - . The analysis will focus on the themes of emigration and colonization and their presentation to the pupils. All the three nations, even if in a different way, were concerned at that time with the leaving of a part of their population migrating in other countries, especially in the Americas, and with the conquest or management of old and new colonies. Through the presentation of emigration and colonization in textbooks it is possible to know the way in which subjects such as nationalism, civilization and race and more generally the relationship with diversity, at European and extra-European level, have been taught and transmitted, generating wars and prejudices that also today are very difficult to eradicate.